The Effect of Company Size, Liquidity and Leverage on Company Performance in the Food and Beverage Sector in Indonesia - Kamila, Nurul; Novialumi, Anita (JURNAL ADMINISTRASI KANTOR, 2023)
This study aims to determine the effect of company size, liquidity, and leverage on the performance of food and beverage sector companies listed on the Indonesia Stock Exchange in the period 2018 to 2022. This research is in the form of panel data with sample selection using purposive sampling so that 18 companies were obtained. The secondary data used is financial statements from the Indonesia Stock Exchange website, this study uses multiple regression analysis methods with the help of SPSS 25 software. The results of this study are for the variable of company size has a negative effect on company performance, liquidity variables do not affect company performance while for variable leverage has a negative effect on company performance .   Keywords: Company Performance, Size, Liquidity, Leverage.